Association between Platelet-Lymphocyte Ratio and Troponin-I in NSTE-ACS Patient - Riyanti, Rini; Sutejo, Ika Rahmawati; Arif, Dina Rizky Amalia (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Non-ST segment elevation acute coronary syndrome (NSTE-ACS) accounts for 2/3 of cases of acute coronary syndrome in the hospitals in United States. Acute coronary syndrome causes myocardial ischemia, which results in the release of cellular elements like cardiac troponin into interstitial and intravascular spaces. Troponin-I is a marker of heart muscle damage with high sensitivity and specificity. Researchers were interested in analyzing the relationship between Troponin-I and the inflammatory biomarkers Platelet-Lymphocyte Ratio (PLR). Complete blood count is a routine test, which provides information about red and white cells as well as platelets and lymphocytes. This study aimed to determine the correlation between PLR and Troponin-I in a patient presenting NSTE-ACS using cross-sectional design and medical records data of patients presenting NSTE-ACS at Slamet Martodirdjo Hospital, Pamekasan from January to December 2022. The correlation between variables was analyzed using Spearman correlation tests. The Spearman test results showed a p-value of 0.132, indicating a very weak positive correlation between PLR and Troponin-I in NSTE-ACS patients at Slamet Martodirdjo Hospital (r= 0.150, very weak correlation). Receiver Operating Characteristic (ROC) curve analysis of PLR to determine infarct (NSTEMI) in NSTE-ACS patients showed a cut-off of 139.5 for PLR with a sensitivity of 57.9% and a specificity of 59.3%.